The crystal prison / 2. - Jarvis, Robin, 1963- (Jarvis, Robin, 1963- Deptford mice, 2001)
The Deptford Mice have arrived in the countryside after being forced to flee the city's rat-infested sewers by the Starwife, an ancient squirrel with unfathomable wisdom and power.